(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
Nutrition surveillance is a system that aims to provide regularly updated information about nutritional status of population and the factors that influence it through the collection, analysis of nutritional data and its factors on a regular and continuous basis. This information provides a basis for those responsible for making decisions for planning, policy formulation, and management of nutrition programs, to determine immediate, short-term and long-term actions or interventions, and to evaluate program effectiveness. Nutrition surveillance as well as surveillance in other fields has three principles of activity, namely data collection (assessment), data processing (analysis) and dissemination of the results of analysis to stakeholders to be utilized in efforts to improve the nutritional status of the community (action). Nutritional Surveillance in Indonesia: Nutritional surveillance in Indonesia was developed in early 1980-1985 with sample locations in Central Lombok district, West Nusa Tenggara and in Boyolali district, Central Java with a focus on developing the Timely Warning Information for Intervention System (TWIIS) or ‘Sistem Isyarat Dini untuk Intervensi’ (SIDI) for efforts to prevent the incidence of food insecurity. After then it was developed to other provinces by changing its name to the Food and Nutrition Surveillance System or ‘Sistem Kewaspadaan Pangan dan Gizi’ (SKPG), and from around 2010 it changed its name to Nutrition Surveillance or ‘Surveilans Gizi’. Both SKPG and Nutrition Surveillance already include utilization of Nutrtional Status Monitoring (PSG) data, and Growth Monitoring data. Problems: Based on the concept of nutritional surveillance activities above, nutrition surveillance is actually an important instrument in providing evidence to increase the effectiveness of nutrition improvement efforts. However, on the other hand, the activities of nutritional surveillance until now are still not clear. For example, data collected regularly and continuously such as growth monitoring data and new school entrant height data (TBABS) have not been optiimally utilized for nutritional surveillance in supporting efforts to overcome the problem of stunting. Included in this is to improve the validity of the collected data. Conclusion: To support efforts to overcome the problem of stunting, nutritional surveillance needs to be revitalizeded so that it can function properly and correctly, including capacity building for implementers in each of the administrative level.